Influence of personality trait on business performance: The mediating role of risk aversion in hybrid tourism entrepreneurs - Shahnawaz Ahmad Dar; Neda Ul Bashir (Tourism)
Even though the occurrence of hybrid entrepreneurs (people who work somewhere else but also own enterprises) is quite common, their personality traits and their influence on business performance have not yet been broadly studied, especially in the context of the tourism industry. Collecting data from tourism entrepreneurs in Jammu and Kashmir (J&K), India, the current study investigates how the Big Five personality traits of tourism hybrid entrepreneurs influence business performance. Further, risk aversion has been investigated through mediation to test whether the association between personality traits and business performance is affected in its presence. To achieve this goal, hierarchical regression analysis was used to study this influence and the results revealed that hybrid entrepreneur extraversion, conscientiousness, and openness to experience produces a favourable influence. In addition, risk aversion partially mediates the association between personality traits and business performance. Further interaction helps in explaining variance in a better way. The current study is the first to present data demonstrating the necessity for hybrid entrepreneurs to be investigated as a distinct category in personality-focused entrepreneurship research.